Confessional Records as a Source of the History of the Pskov Church and Clergy of the 1727-1762 - Postnikov Arsenii (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The task of the article is to introduce of the new mass sources for the research of the Pskov church and clergy into the scientiﬁc circulation. The work is based on the Pskov confessional records of the 1727–1762, kept in State Archive of the Pskov Region (SAPR), for the ﬁrst time raised in full amount for research. The general historiography on the subject as well as history of introduction of the confessional records into church usage are presented in the article. Results of systematization of the confessional records given have aﬀorded to deﬁ ne the cast of the functioning parishes in Pskov. As a whole it was identiﬁed 597 confessional records of 57 “Pskov Town” churches for the period of research. They contain the extensive knowledge on the personnel of Church clergy and the number of white clergy in Pskov during the ﬁrst decades of the synod period in the Russian Orthodox Church history. On their basis it is possible to ﬁnd out about the time and periods of clergy personnel’s service in every temple, about movements by the “ladder of ranks”, that shows life path of the clergy representatives in the years when there was no service records and clergy accounts, containing biography data. The remarkable feature of the confessional records is that they are the ﬁ rst source to appear by time where with the highest degree of completeness the people “spiritual and their household” were taken into account. There are data given here about all members of the priesthood and clergy families and their age (including female part), that opens the wide opportunities for reconstruction of the clergy representatives’ genealogies and study of the spiritual estate as a whole. Refs 16 names.